Development of mixed matrix ZIF-8/polyvinylidene fluoride membrane with improved performance in solvent resistant nanofiltration - Karimi, Atefeh; Khataee, Alireza; Safarpour, Mandie; Vatanpour, Vahid (Elsevier, 2020)
In the present study, the incorporation of zeolitic imidazolate framework 8 (ZIF-8) as an inorganic additive in the matrix of polyvinylidene fluoride (PVDF) membranes was investigated. The ZIF-8/PVDF mixed matrix membranes were prepared with 5, 10. 15, 20, and 25 wt% ZIF-8 and characterized using SEM, EDX, and AFM analyses. The fabricated membranes then were utilized in solvent resistant nanofiltration (SRNF) process for removal of Rose Bengal (RB) from ethanol and isopropanol (IPA). The modified mixed matrix membranes (MMMs) containing 25 wt% of ZIF-8 represented a rejection of 99.5% for RB solution in the IPA, which is 15% more than the bare PVDF membrane. 4.1% flux reduction was observed for blended membranes with 25 wt% of ZIF-8 during filtration of RB solution in the IPA, whereas this reduction was 16.1% for the bare PVDF membrane. The results of swelling studies revealed that the ZIF-8 modified membranes had a lower swelling degree in both ethanol and IPA solvents compared with bare PVDF due to the reduced available space for the diffusion of large molecules.
Keywords: Zeolitic imidazolate framework-8; PVDF; Mixed matrix membranes; Solvent resistant nanofiltration; Rose Bengal